Label-free single molecule imaging with numerical aperture-shaped interferometric scattering microscopy - Cole, D; Young, G; Weigel, A; Kukura, P (American Chemical Society, 2017)
Our ability to optically interrogate nanoscopic objects is controlled by the difference between their extinction cross sections and the diffraction-limited area to which light can be confined in the far-field. Here, we show that a partially transmissive spatial mask placed near the back focal plane of a high numerical aperture microscope objective enhances the extinction contrast of a scatterer near an interface by approximately T^-1/2, where T is the transmissivity of the mask. Numerical aperture-based differentiation of background from scattered light represents a general approach to increasing extinction contrast and enables routine label-free imaging down to the single molecule level.